ТАРИЙХЫЙ ҚОСЫҚЛАР – ХАЛЫҚ ҚОСЫҚЛАРЫНЫҢ АЙРЫҚША БИР ТҮРИ СЫПАТЫНДА - Қанаатов, Е.Е. (ILIM hám JÁMIYET, 2020)
The article highlights the features of the Karakalpak historical songs as a separate type of folk songs. Until now, in the classification of genres of Karakalpak folklore, historical songs and historical djirs were considered one type. The author believes that the historical song is lyrical, and the historical djir is a part of a series of epic works, and suggests considering them as such.